Electrostatic complementarity in pseudoreceptor modeling based on drug molecule crystal structures: the case of loxistatin acid (E64c). (4th November 2014) - Shi, Ming W.; Sobolev, Alexandre N.; Schirmeister, Tanja; Engels, Bernd; Schmidt, Thomas C.; Luger, Peter; Mebs, Stefan; Dittrich, Birger; Chen, Yu-Sheng; Bąk, Joanna M.; Jayatilaka, Dylan; Bond, Charles S.; et al.
Abstract : A combination of pseudoreceptor modeling and electrostatic complementarity maps properties of a native pocket for an enzyme ligand. Abstract : After a long history of use as a prototype cysteine protease inhibitor, the crystal structure of loxistatin acid (E64c) is finally determined experimentally using intense synchrotron radiation, providing insight into how the inherent electronic nature of this protease inhibitor molecule determines its biochemical activity. Based on the striking similarity of its intermolecular interactions with those observed in a biological environment, the electrostatic potential of crystalline E64c is used to map the characteristics of a pseudo-enzyme pocket.